Necessity of Evil. Proof by Contradiction (Supplement to Alvin Plantinga) - Kwaśniewski, Jacek (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The Christian tradition sees the evil as a by-product of our free will. However, this thesis could simply rejected as it can be argued that there is no logical contradiction in the existence of beings who would act freely but always go right. Hitherto attempts to point out the fallacy of this rejection failed. My proof by contradiction solves the problem. I assume that beings having free will can do only good. Next I show that such a possibility must lead to the rejection of their free will in the selection of their hierarchy of values. Therefore the thesis of free beings doing always good results in contradiction. Therefore, the evil is unavoidable.